2016
DOI: 10.1016/j.csse.2016.05.005
|View full text |Cite
|
Sign up to set email alerts
|

Fundamental period elongation of a RC building during the Pollino seismic swarm sequence

Abstract: a b s t r a c tA primary school in Rotonda was monitored during an on-going seismic sequence in the Pollino area, Southern Italy. The Reinforced Concrete (RC) building is a typical three story building with a concrete frame, bearing pre-cast slab flooring, concrete block internal walls and pre-cast external infill slabs. The monitoring began in September 2011 with a single station on top of the building, and after the M L = 5 mainshock occurred in October 2012 a network was completed with accelerometers on eac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 30 publications
0
10
0
Order By: Relevance
“…24,25 On one hand, we have examples such as the Navelli town hall, which suffered the 2009 Abruzzo earthquake, 26 and the primary school in the Rotonda city struck by the 2010–2014 Pollino swarm. 3 In both cases, the buildings showed multiple temporary period elongations which did not reflect in any increased damage. On the other hand, a permanent period shift accompanied by damage was observed both at a reinforced concrete building located in Bonefro during the 2002 Molise earthquake (Mucciarelli et al, 2004) and at the Mirandola hospital during the 2012 Emilia earthquake.…”
Section: Introductionmentioning
confidence: 92%
See 3 more Smart Citations
“…24,25 On one hand, we have examples such as the Navelli town hall, which suffered the 2009 Abruzzo earthquake, 26 and the primary school in the Rotonda city struck by the 2010–2014 Pollino swarm. 3 In both cases, the buildings showed multiple temporary period elongations which did not reflect in any increased damage. On the other hand, a permanent period shift accompanied by damage was observed both at a reinforced concrete building located in Bonefro during the 2002 Molise earthquake (Mucciarelli et al, 2004) and at the Mirandola hospital during the 2012 Emilia earthquake.…”
Section: Introductionmentioning
confidence: 92%
“…50 With this strategy, building frequency variations, either during or after an earthquake, can be easily observed, hence obtaining an immediate indication of the damage evolution. 3,26…”
Section: Shmmentioning
confidence: 99%
See 2 more Smart Citations
“…Clinton et al [16] and Astorga et al [17] showed the accumulated effect of successive earthquakes on frequency drop, in relation to the amplitude of seismic loading, for long-term structural monitoring. Furthermore, Gallipoli et al [18] reported the co-seismic frequency drop of permanent monitored buildings during main and aftershocks. Post-earthquake experimental surveys for building damage classification have also highlighted residual elongations.…”
Section: Introductionmentioning
confidence: 99%